URBAN STUDIES: UNIVERSAL INTERDISCIPLINARY STRATEGIES - Maryna Prepotenska; Vania Angelova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The article deals with the specifics of the urban studies teaching in an interdisciplinary field. The authors present two teaching strategies that are universal in their interdisciplinary coverage: the method of mental maps and the concept of the revitalisation of urban locations in terms of theoretical comprehension and practical implementation. Students receive a task typical for a case method: to map the city on the basis of their experiences and preferences and comment on the results. The authors have found out that this process shows not only the urban visual representation, but reflects the existential level of each participant, his/her mental, spiritual, and bodily potential. The authors determine such leading intentions in mastering the city as consumerism (43%), soulfulness (21%), aestheticism (15%), co-creation (13%) and existential closeness (8%). Each type of social behaviour has a wide range of determinants that can be a subject to analysis of a number of disciplines in the sphere of humanities. The stage of perception and practice of the process of revitalisation represents a logical transition from analytical studies to social interaction, which is able to unite participants of urban studies in co-creation in real time. With this in mind, authors claim that some students develop their outlook and communication in the framework of the "creative class" in the "creative city". Since the method of mental maps and revitalisation exceed the traditional content of these approaches, the article proposes to introduce the term SENSITIVE MAP, reflecting the development of the city on the basis of the "sense of the city" and the meaning of the city residents' life values.